A Scalable Interfacial Engineering Strategy for a Finely Tunable, Homogeneous MoS2/rGO‐Based HER Catalytic Structure. Issue 9 (2nd April 2020) - Xu, Linan; Zhang, Yihe; Feng, Lili; Li, Xin; An, Qi
Abstract: The electronic structures and catalytic efficacies of molybdenum disulfide (MoS2 )‐based catalysts are sensitive to embedding environment. In order to develop a finely tunable strategy, a "layer‐by‐layer and Nafion capping" strategy for the scalable preparation of interfacial (MoS2 )‐based catalytic structures is developed. The study shows that the assembly partner influences the electronic structures of the Zn&N co‐doped (MoS2 ) (Zn‐N‐(MoS2 )) catalysts. Poly(allylamine hydrochloride) (PAH) decreases the catalytic efficacy, whereas when PAH‐rGO (rGO [reduced graphene oxide]) is the assembly partner, effective interfacial catalysts are prepared. The superior catalytic efficacy of (PAH‐rGO/Zn‐N‐(MoS2 ))n can be attributed to the fact that rGO effectively activates the basal plane S 2− as the active sites. The catalytic efficacy of the multilayers at 16 assembly cycles due to a balance between the number of active sites and low resistance. After capping with Nafion layer, the interfacial catalysts exhibit high stability. Compared with the widely used drop‐casting methods, the layer‐by‐layer strategy possesses unique benefits, including fine‐tune the structures, free choice of the partner, and planar homogeneity. It is expected that this layer‐by‐layer catalyst immobilization strategy will benefit fundamental understandings regarding the finely controlled scalable interfacial immobilization of catalysts with superior efficacy, and assist in promoting the practical utilization of various catalysts. Abstract : A "layer‐by‐layer and Nafion capping" strategy for the scalable preparation of interfacial MoS2 ‐based catalytic structures on various substrates is developed. The reason for the superior catalytic efficacy of the (PAH–rGO/Zn–N–MoS2 ) n assembly is that reduced graphene oxide (rGO) effectively activates the basal plane S 2− as the active sites, instead of the widely believed interfacial resistance decreasing effects by adding rGO.